Investment and financial restraints: theory and evidence - Devereux, M; Demetriades, P (2000)
This paper examines investment decisions in an economy with two financial markets: an official market, which is subject to rationing due to an interest rate ceiling, and an unrestricted market, with a higher interest rate. In this context, the long-run equilibrium aggregate capital stock is unambiguously higher than in the absence of the interest rate ceiling, even though its relationship with the ceiling is non-monotonic. Empirical results using aggregate panel data from 52 developing countries for the period 1974–1988 provide support for the model, particularly in economies that have some access to international capital markets.